Cultural journalism and disability in cinema: A view of its historical evolution through specialized critique - García-Borrego, Manuel; González-Cortés, María Eugenia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The aim of this paper is to describe the evolution of disability in cinema via its relationship with the specialized press. We analysed all movies’ data sheets from ‘Filmaffinity’ (n=1,180), together with all the professional reviews highlighted in them (n=2,000). The results show a preponderance of drama over other genres, although it is documentaries that obtain the best reception from cultural press. Women and Anglophone media tend to value these productions more favourably. In addition, the quality of the records, according to these experts, increases year after year.